Broadway goes to war : American theater during World War II - McLaughlin, Robert L., 1957-2022; Parry, Sally E. (University Press of Kentucky, 2021)
"In Broadway Goes to War, Robert L. McLaughlin and Sally E. Parry analyze how American theater actively addressed and debated timely and controversial topics during World War II. Productions such as Watch on the Rhine (1941), The Moon is Down (1942), Tomorrow the World (1943), and A Bell for Adano (1944) encouraged public discussion of the war's impact on daily life and raised critical topics about the conflict well before other forms of popular media. McLaughlin and Parry reveal that while film studios, radio stations, newspapers, and other media outlets widely chose to echo official government communications and opinions regarding Nazi Germany and the war, Broadway remained stunningly independent. In the absence of pressure from the US Office of War Information or an industry-based agency like Hollywood's Hayes Office, the New York stage became an important venue for debating topics that would have been considered taboo on a film set, including neutrality and isolationism, racism and genocide, and heroism and battle fatigue. American drama of the 1940s is frequently overlooked, but the plays performed during this eventful decade provide a picture of the rich and complex experience of living in the US during the war years. McLaughlin and Parry's work fills a significant gap in the history of theater and popular culture, showing that American society was more divided and less idealistic than the received histories of the WWII home front and the entertainment industry recognized"--